2017
DOI: 10.1371/journal.pone.0183463
|View full text |Cite
|
Sign up to set email alerts
|

Adult hippocampal neurogenesis poststroke: More new granule cells but aberrant morphology and impaired spatial memory

Abstract: Stroke significantly stimulates neurogenesis in the adult dentate gyrus, though the functional role of this postlesional response is mostly unclear. Recent findings suggest that newborn neurons generated in the context of stroke may fail to correctly integrate into pre-existing networks. We hypothesized that increased neurogenesis in the dentate gyrus following stroke is associated with aberrant neurogenesis and impairment of hippocampus-dependent memory. To address these questions we used the middle cerebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
71
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 28 publications
9
71
4
Order By: Relevance
“…The presence of neuroblasts in the hippocampal hilus may represent ectopic migration of adult-born cells to this hippocampal region. This has been reported after status epilepticus (Yang et al, 2008) and stroke (Woitke et al, 2017).…”
Section: )supporting
confidence: 52%
“…The presence of neuroblasts in the hippocampal hilus may represent ectopic migration of adult-born cells to this hippocampal region. This has been reported after status epilepticus (Yang et al, 2008) and stroke (Woitke et al, 2017).…”
Section: )supporting
confidence: 52%
“…To our knowledge this is the first study showing that obesity/T2D impairs stroke-induced hippocampal neurogenesis. The functional role of hippocampal neurogenesis in the overall recovery of impaired hippocampal function after stroke is largely unknown, although studies suggest it is limited or even harmful, mainly due to the limited ability of new neurons to integrate in neuronal networks properly [51,78]. However, recent animal studies have shown that T2D decreases cognitive functions after stroke [10,79], also by employing HFD feeding [22,80].…”
Section: Discussionmentioning
confidence: 99%
“…14,15). Although subgranular zone (SGZ) neurogenesis could promote cognitive function recovery after cerebral ischemia (16,17), stroke also modifies the morphology of newborn granule cells (18,19), concomitant to hippocampus-dependent memory deficits, suggesting a role of hippocampal neurogenesis in poststroke cognitive impairment. Furthermore, higher levels of hippocampal neurogenesis promote forgetting of old memories, which are otherwise strengthened by reducing neurogenesis (9,20).…”
Section: Introductionmentioning
confidence: 99%